THE USAGE OF THE EPONYM IN MARKETING FIELD - Xamidova Azizakhon Umidjon qizi (Bright Mind Publishing, 2025)
This article reveals the term of eponym in English language.The given definition reveals the features of the term eponym which is named after someone or the name of place can be meticuliously investigated. Most terms of eponomy can be used in economical spheres or the names of brands. Through definition analysis, it became possible to identify the linguistic problems associated with eponyms, which will be demonstrated in the results and discussion section.
Keywords: Eponomy, boycott, toponomy, concept, proper name, denote.